2012
DOI: 10.1007/s10552-012-0029-4
|View full text |Cite
|
Sign up to set email alerts
|

Metropolitan area racial residential segregation, neighborhood racial composition, and breast cancer mortality

Abstract: Racial residential segregation may influence health for blacks and whites differently. Pathways through which RRS patterns impact health should be further explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 41 publications
4
63
1
Order By: Relevance
“…Numerous studies have shown that persistent residential racial-ethnic segregation in the United States serves as both a health promoter by facilitating stronger social support networks and as a health barrier by fostering conditions that limit resources (16, 39, 45, 46). Racial–ethnic composition in this study was based on ZCTAs having >50% Hispanic, >50% NHW, >50%NHAsian-Pacific Islander (NHAPI), >50% NHB, >50%NH American Indian/Native Alaskan, or mixed (NHM), if not any of the previous.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have shown that persistent residential racial-ethnic segregation in the United States serves as both a health promoter by facilitating stronger social support networks and as a health barrier by fostering conditions that limit resources (16, 39, 45, 46). Racial–ethnic composition in this study was based on ZCTAs having >50% Hispanic, >50% NHW, >50%NHAsian-Pacific Islander (NHAPI), >50% NHB, >50%NH American Indian/Native Alaskan, or mixed (NHM), if not any of the previous.…”
Section: Methodsmentioning
confidence: 99%
“…In breast cancer patients, low neighborhood socioeconomic status (SES) predicts worse all-cause and non-breast-cancer-specific survival above and beyond the effects of individual SES (Lian et al, 2014); these associations may, however, vary by race/ethnicity (Shariff-Marco et al, 2014). African American women with breast cancer living in metropolitan areas with higher levels of racial segregation are at increased risk of mortality from breast cancer compared to White women living in those same metropolitan areas (Russell et al, 2012). In addition, breast cancer patients living in census tracts with a high risk of home foreclosure reported worse self-rated health than women living in areas with low foreclosure risk; this association was explained by lower income, lower physical activity levels, and worse perceived neighborhood conditions (Schootman, Deshpande, Pruitt, & Jeffe, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Russell et al [31] observed a strong correlation between breast cancer mortality and survival for blacks vs. whites in metropolitan cities. Collins and Williams [32] identified an association between residential segregation and mortality across 107 major U.S. cities and found that racial isolation was associated with all-cause and cancer mortality for African Americans, even after adjusting for socioeconomic indicators.…”
Section: Introductionmentioning
confidence: 99%